2018
DOI: 10.1016/j.molcel.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The PLAG1-GDH1 Axis Promotes Anoikis Resistance and Tumor Metastasis through CamKK2-AMPK Signaling in LKB1-Deficient Lung Cancer

Abstract: Loss of LKB1 is associated with increased metastasis and poor prognosis in lung cancer, but the development of targeted agents is in its infancy. Here we report that a glutaminolytic enzyme, glutamate dehydrogenase 1 (GDH1), upregulated upon detachment via pleomorphic adenoma gene 1 (PLAG1), provides anti-anoikis and pro-metastatic signals in LKB1-deficient lung cancer. Mechanistically, the GDH1 product α-KG activates CamKK2 by enhancing its substrate AMPK binding, which contributes to energy production that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(189 citation statements)
references
References 46 publications
2
166
0
Order By: Relevance
“…CaMKK2 and its downstream kinases, CaMKI, CaMKIV, and AMPK have well-established roles in energy homeostasis, nutrient responses, and cell growth (Marcelo et al, 2016). Furthermore, CaMKK2 is upregulated in multiple tumor types, and its inhibition reduces cell proliferation and tumorigenicity in vivo (Lin et al, 2015;Jin et al, 2018). Our work reveals that, in addition to receptors for circulating factors, such as hormones and metabolites (Swulius and Waxham, 2008;Marcelo et al, 2016), also mechanical stimuli can activate CaMKK2 in cells.…”
Section: Discussionmentioning
confidence: 74%
“…CaMKK2 and its downstream kinases, CaMKI, CaMKIV, and AMPK have well-established roles in energy homeostasis, nutrient responses, and cell growth (Marcelo et al, 2016). Furthermore, CaMKK2 is upregulated in multiple tumor types, and its inhibition reduces cell proliferation and tumorigenicity in vivo (Lin et al, 2015;Jin et al, 2018). Our work reveals that, in addition to receptors for circulating factors, such as hormones and metabolites (Swulius and Waxham, 2008;Marcelo et al, 2016), also mechanical stimuli can activate CaMKK2 in cells.…”
Section: Discussionmentioning
confidence: 74%
“…We found that cholangiocarcinoma cells with differential RMP expression did not show differences in proliferation or migration under 2D culture conditions in vitro , although RMP overexpression promoted an increase in the colony formation capacity in a soft agar 3D environment of stimulation. After epithelial cells detach from the basement membrane, anoikis tends to occur, and some cells can continue to resist this apoptosis, showing anchorage‐independent growth . It has been reported that cells must surmount different kinds of stress, including increased ROS levels, to maintain anchorage‐independent growth .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these authors used 5-fold greater concentrations of palbociclib to our own which is above the safe plasma C max concentration, and our ability of palbociclib to enhance AMPKα T172 phosphorylation occurs in cells with very low/no LKB-1 expression such as HT1080 (sarcoma), A549 and H460 (NSCLC) and HCT116 (colon). 21 However, others have reported that palbociclib in a CDK4/6-independent fashion activates the AMPK. 22 And, that this effect may be due to inhibition of other targets such as CDK9, which has a similar consensus sequence to that of CDK4/6 and ERK1/2.…”
Section: Discussionmentioning
confidence: 99%